PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA INTERAKTIF MENGGUNAKAN ADOBE FLASH CS 5 POKOK BAHASAN TRIGONOMETRI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS X SMA - Nuryadi Nuryadi; Zulfa Hanani Bahtiar (AlphaMath : Journal of Mathematics Education, 2017)
This research aims at 1) developing interactive media for mathematics learning by using Adobe Flash CS 5 in trigonometry material to enhance students’ learning motivation; 2) recognizing the media quality through validity, practicality, and effectiveness. The used of research design is research and development (R&D) which adapted the steps from Borg and Gall. These steps consist of three steps as introduction, development, and validation. This research shows that the applied media is useable which assessed through aspect of validity, practicality, and effectiveness of interactive learning media. Keywords: Adobe Flash CS 5, learning motivation, mathematics learning media